1993
DOI: 10.1159/000236401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Pseudomonas aeruginosa</i> Alginate on <i>Escherichia col</i><i>i</i>- and <i>Staphylococcus aureu</i><i>s</i>-lnduced Inflammatory Mediator Release from Human Cells

Abstract: We analyzed the role of soluble purified Pseudomonas aeruginosa alginate on Escherichia coli K-12 (pANN5211) as well as on Staphylococcus aureus 121c-induced inflammatory mediator release from human platelets, granulocytes, and basophils. In the presence of alginate (1–4 mg/ml), the mucoid exopolysaccharide of P. aeruginosa, the bacteria-induced inflammatory mediator release was modulated as follows: (1) the E. coli- as well as S. aureus-induced chemiluminescence response from human neutrophils increased 2- to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
(22 reference statements)
1
12
0
1
Order By: Relevance
“…We have previously shown that in contrast to nonmucoid P. aeruginosa mucoid P. aeruginosa strains as well as puri fied alginate inhibit the generation of the chemotactic LTB4 [19,20,25]. In the present study we show that ( 1 ) P. aerugi nosa bacteria, mucoid and nonmucoid, are able to induce the generation of the chemotactic IL-8 from human phago cytes, and P aeruginosa alginate does not inhibit IL-8 re lease from human phagocytes.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations
“…We have previously shown that in contrast to nonmucoid P. aeruginosa mucoid P. aeruginosa strains as well as puri fied alginate inhibit the generation of the chemotactic LTB4 [19,20,25]. In the present study we show that ( 1 ) P. aerugi nosa bacteria, mucoid and nonmucoid, are able to induce the generation of the chemotactic IL-8 from human phago cytes, and P aeruginosa alginate does not inhibit IL-8 re lease from human phagocytes.…”
Section: Discussionsupporting
confidence: 39%
“…Mucoid in contrast to nonmucoid P. aeruginosa strains failed to induce the chemotactically active LTB4 [20,25]. Thus, we compared the capacity of CF3 and CF3M strains to induce IL-8 from PMN and PBMC.…”
Section: Il-8 Release By Professional Phagocytes (Granulocytes Monocmentioning
confidence: 98%
See 2 more Smart Citations
“…exotoxin A, exoenzyme S. cytotoxin, the mucoid exopolysaccharide (alginate), the heat-labile (phospholipase C) as well as the heat-stable hemolysin (glycolipid) and at least two different proteases [4][5][6][7], Recently, we have shown that the interaction be tween pathogenicity factors, e.g. the P aeruginosa algi nate and the hemolysins of Escherichia coli, Staphylococ cus aureus and Serratia marcescens, may contribute to the pathophysiological understanding of P. aeruginosa infec tion in CF [8]. Nonetheless, in CF there is as yet no satis factory explanation for the deleterious outcome of the chronic Pseudomonas infection which is characterized by a massive lung infiltration with neutrophils as well as local destruction of lung tissue [3,9],…”
mentioning
confidence: 99%